Evaluación de la analgesia intraoperatoria y postoperatoria en combinación de ketamina, fentanilo, lidocaína y ketamina, morfina en perros sometidos a distintos tipos de procedimientos quirúrgicos - Macao Quezada, Cristina Lizbeth (2024)
During surgery, actions such as incisions of tissue, bone, nerves, among others, transmit harmful afferent stimuli from the periphery to the spinal cord, inducing a prolonged state of central neural sensitization or hyperexcitability, amplifying the wound stimuli and increasing postoperative pain. This research was carried out with the purpose of evaluating intraoperative pain in patients undergoing different surgical procedures. There were 3 groups, each with 5 patients and with different intraoperative infusions. In each group, a traumatology procedure, ovariohysterectomy, splenectomy, paralytic ileus and hernia resolution were performed. Group 0 (n=5) was the control group. Group 1 (LFK) (n=5) received fentanyl 2 ml (0.03 ug/kg/min), lidocaine 7.5 ml (50 ug/kg/min) and ketamine 0.3 ml (10 ug/kg/min). In group 2 (KM) (n=5), morphine 1 ml (3.3 ug/kg/min) and ketamine 0.3 ml were diluted (10 ug/kg/min). Each infusion was diluted in 500 ml of saline and dosed at 10 ml/kg/hour. During the surgical procedures the following physiological signals were recorded: heart rate (HR), oxygen saturation (SpO2), body temperature (T°), systolic blood pressure (SBP) and diastolic blood pressure (DBP). Postoperative pain was measured using the Glasgow composite measure pain scale (CMPS) and Quantitative sensory testing (QST). In conclusion, the LM and LFK protocols yielded good analgesia during the intraoperative period. Variables such as temperature showed more differences between groups, SBP in the LM group caused hypotension, and heart rate in group 0 showed tachycardia. In the CMPS and QST, better sensitivity to touch was observed, thus confirming the analgesia of both protocols.